2012
DOI: 10.1002/ijc.27490
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glycogen synthase kinase‐3 by thymosin beta‐4 is associated with gastric cancer cell migration

Abstract: Thymosin beta-4 (Tb4), actin-sequestering protein, plays important roles in many cellular functions including cancer cell migrations. Glycogen synthase kinase (GSK) in Wnt signaling pathway is a key molecule to control intercellular interaction. Here, we investigated whether GSK-3 activity is regulated by Tb4 and it is associated with Tb4-mediated migration in gastric cancer cells. Various expression level of Tb4 was observed in human gastric tumor tissues. Migration in gastric cancer cells, SNU638 and SNU668,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 49 publications
(115 reference statements)
2
34
0
Order By: Relevance
“…We found TIPE1 inhibited the expression of Wnt1, a secreted ligand that activates Wnt signalling pathways, which strongly correlates with tumorigenesis and progression [23,25]. Activation of Wnt signalling pathway can promote b-catenin, a key regulator of the Wnt pathway, nuclear translocation through increasing phosphate GSK3b [26]. Indeed our results showed the amount of phosphorylated GSK3b and active b-catenin (dephosphorylated b-catenin) was dramatically inhibited by TIPE1.…”
Section: Discussionmentioning
confidence: 61%
“…We found TIPE1 inhibited the expression of Wnt1, a secreted ligand that activates Wnt signalling pathways, which strongly correlates with tumorigenesis and progression [23,25]. Activation of Wnt signalling pathway can promote b-catenin, a key regulator of the Wnt pathway, nuclear translocation through increasing phosphate GSK3b [26]. Indeed our results showed the amount of phosphorylated GSK3b and active b-catenin (dephosphorylated b-catenin) was dramatically inhibited by TIPE1.…”
Section: Discussionmentioning
confidence: 61%
“…Previous research reported that ILK mediated Hh signaling by regulating the localization of SMO in the cilium 30 . It also demonstrated that TB4 stabilized ILK in cardiomyocyte and colon cancer cells and that overexpression of TB4 inactivated GSK3B by hyper-phosphorylating GSK3B 3133 .…”
Section: Introductionmentioning
confidence: 91%
“…Recently, numerous studies have reported that Tβ4 has multiple biological activities to promote angiogenesis (Grant et al 1995(Grant et al , 1999, chemotaxis (Tokura et al 2011), and wound healing (Philp et al 2004). Apparently, human gastric cancer cells, such as SNU668, showing a higher expression level of Tβ4 have a higher migratory potential compared to SNU638 cells showing relatively low expression of Tβ4 (Ryu et al 2012). Upregulation of Tβ4 expression has also been found in melanoma cell lines isolated from metastatic tumors and in clinical metastatic melanoma tissues (Nummela et al 2006).…”
Section: Introductionmentioning
confidence: 95%